EFFECT OF CALCIUM CHLORIDE ON HIGHWAY SUBGRADE SOIL CONTAINING HIGH SOLUBLE SALTS - Farhan Ibrahim, Saad; Hadi A. Ali, Abdulhaq; Salah Ibrahim, Mohammed (Journal of Engineering and Sustainable Development, 2015)
The quality of the subgrade will greatly influence the pavement design and the service life of the pavement. This study is performed to evaluate the effect of Calcium Chloride (CaCl2) on the strength of subgrade soil containing high percentage of soluble salts. The soil sample brought from Al-mahmodia city south of Baghdad, it contains about (15.685%) of soluble salts by weight of soil content. California Bearing Ratio (CBR) value is determined for the natural soil and Calcium Chloride (CaCl2) with different number of blow per layer (10, 25 and 56) for (4-days) soaking periods to achive CBR value at 95% relative modified proctor. Durability tests (effect of long term soaking and drying) for the subgade stabilized with (2.5% CaCl2) and compacted at 95% relative modified proctor is determined, the soaking periods are (4, 7, 14, 28, 60 days), the results of soaking periods are ( 7.961, 6.446, 4.436, 3.398, 2.427) respectively and the results of soaking and drying periods are ( 8.258, 6.531, 4.563, 3.511, 2.621). The results of soaking and drying show reduction in both (CBR) value and (T.S.S) with the time.